What Is a 'Bug'? - Widder, David Gray; Goues, Claire Le (Communications of the ACM, 2024)
This article delves into the definition of bugs in software with an emphasis on subjectivity and judgment. Topics include Hyrum’s law, epistemology, and epistemic power. The article provides two examples dealing with gender and software use and ethics and closes with suggestions for software research and practice.